Responses of bimetallic Ag/ZnO alloy nanoparticles and urea on morphological and physiological attributes of wheat - Maria Ehsan; Naveed Iqbal Raja; Zia‐ur‐Rehman Mashwani; Muhammad Ikram; Efat Zohra; Syeda Sadaf Zehra; Fozia Abasi; Mubashir Hussain; Muhammad Iqbal; Nilofar Mustafa; Asad Ali (IET Nanobiotechnology)
Abstract Wheat (Triticum aestivum L.) is the most important staple food crop globally. According to economic survey 2018‐19, agriculture sector of Pakistan grew by 0.85%, with wheat accounting for 8.9% of agriculture and 1.6% of GDP, and its production fell short of the target by 4.9%. Wheat requires beneficial ties to improve its efficiency with the help of modern technology. Nanotechnology modifies conventional agricultural practices as these are stimulating agents for plant growth. Green bimetallic Ag/ZnO alloy nanoparticles (NPs) synthesised from salts reduced by Moringa oleifera and characterised by UV‐visible spectroscopy, scanning electron microscopy, and energy‐dispersive X‐ray spectroscopy are studied herein. Different concentrations of urea and Ag/ZnO alloy NPs were applied exogenously to wheat plants (Pakistan‐13 and Galaxy13). A significant effect of 100 mg/L urea and 75 ppm Ag/ZnO alloy NPs was observed on the morphology of wheat, with a maximum increase of 58% plant length, 85% leaf area, 89% plant fresh weight and 76% plant dried weight. In physiological parameters, relative water content and membrane stability index have shown maximum increases of 39% and 77%, while chlorophyll a, b, and total chlorophyll content (TCC) showed maximum increases of 92%, 71%, and 84% respectively. Evidence of the morpho‐physiological responses of urea and green synthesised alloy NPs on wheat varieties are reported on.